2008
DOI: 10.4049/jimmunol.181.11.8170-a
|View full text |Cite
|
Sign up to set email alerts
|

Hemopoietic cell expression of the chemokine decoy receptor D6 is dynamic and regulated by GATA1

Abstract: This information is current as by GATA1 decoy receptor D6 is dynamic and regulated Hemopoietic cell expression of the chemokine

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
74
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(78 citation statements)
references
References 49 publications
3
74
0
Order By: Relevance
“…In agreement with recent studies in mice, 11,12) the patient monocyte QPCR data also demonstrated expression of D6 on monocytes, although at relatively low levels. Intriguingly, as shown in Figure 3, Chemokine Decoy Receptor D6 transcript levels were lower in the intermediate monocytes of STEMI patients with diabetes compared to STEMI patients without diabetes (0.25 ± 0.13 versus 0.46 ± 0.16, P < 0.001) and no statistical significance was observed in the other two subsets of monocytes between the STEMI patients with or without diabetes.…”
Section: Resultssupporting
confidence: 78%
“…In agreement with recent studies in mice, 11,12) the patient monocyte QPCR data also demonstrated expression of D6 on monocytes, although at relatively low levels. Intriguingly, as shown in Figure 3, Chemokine Decoy Receptor D6 transcript levels were lower in the intermediate monocytes of STEMI patients with diabetes compared to STEMI patients without diabetes (0.25 ± 0.13 versus 0.46 ± 0.16, P < 0.001) and no statistical significance was observed in the other two subsets of monocytes between the STEMI patients with or without diabetes.…”
Section: Resultssupporting
confidence: 78%
“…We have demonstrated that GATA1 is a physiological regulator of D6 expression [75] using mice with a conditional deletion in GATA1 [78]. In DC of these mice, the knockdown of GATA1 is associated with a transcriptional switch-off of D6 expression confirming a role for GATA1 in the regulation of D6 expression.…”
Section: Regulation Of D6 Expressionmentioning
confidence: 81%
“…As mentioned above such a role is unlikely to be filled by LECexpressed D6. We have now characterised the expression of D6 by leukocytes and it is apparent from this analysis that the role of leukocytes as vehicles for D6 function may not be as straightforward as we had initially appreciated [75,76]. …”
Section: D6 Expression By Leukocytesmentioning
confidence: 99%
“…D6, the best described chemokine decoy receptor (6), is a constitutively internalizing receptor expressed by lymphatic endothelial cells (11), trophoblast cells (12), and, at lower levels, some leukocyte subsets (13). D6 selectively recognizes and degrades most inflammatory CC chemokine agonists of CCR1 to CCR5 (10).…”
mentioning
confidence: 99%